Relationship between trauma mechanism and etiology on mandibular fracture patterns - Fakhrurrazi Fakhrurrazi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Mandibular fracture occurs more commonly than maxillary fracture because of its prominent position and its arrow arch like bone anatomy. Many factors may cause mandibular fracture. Motorcycle accident is the main etiology of mandibular fracture in the world. Based on the literature, 43% mandibular fractures are caused by motorcycle accident, 34% by violence, 7% by accident at work, 7% by fall, 4% by sports and the others were caused by various things. Purpose: The purpose of this study was to know the relation between the etiology and mechanisms of trauma and the patterns of mandibular fracture at Hasan Sadikin Hospital, Bandung, from January 2006 to October 2007. Method: The study was taken on patients with mandibular fractures who came to Hasan Sadikin Hospital Bandung. The data were taken retrospectively by documenting the etiologies of mandibular fracture, the mechanisms of fracture, and the location of mandibular fracture. The data were analyzed with Chi Square statistic test. Result: The result showed that There were 83 mandibular fractures. The mandibular fracture more commonly attacks men about 77%, and women about 22.9%. Mandibular fracture occurs more often between the age group of 21-30 years old, about 31 people (37.3%). Mandibular fracture was mostles often caused by motorcycle accident, affecting about 71 people (85.5%). Parasymphysis fracture is the most common fracture location among mandibular fracture cases, about 47 people (56.6%). Conclusion: It can be concluded that there is no significant relationship between the etiology and mechanisms of trauma and the pattern of mandibular fracture.Latar belakang: Fraktur mandibula lebih sering terjadi dibandingkan dengan fraktur maksilla karenaposisinya yang lebihprominen dan bentuk anatomi tulang seperti busur panah. Banyak faktor yang dapat menyebabkan terjadinya fraktur mandibula. Kecelakaan kendaraan bermotor merupakan etiologi utama penyebab fraktur mandibula di dunia. Literatur menyebutkan bahwa 43% fraktur mandibula disebabkan oleh kecelakaan kendaraan bermotor, 34% disebabkan oleh kekerasan, 7% kecelakaan kerja, 7% akibat jatuh, 4% pada kecelakaan olahraga dan sisanya oleh bermacam-macam sebab lainnya. Tujuan: penelitian ini untuk mengetahui apakah ada hubungan antara etiologi dan mekanisme trauma dengan pola fraktur mandibula pada penderita fraktur mandibula di Rumah Sakit Hasan Sadikin Bandung dari bulan Januari 2006 sampai Oktober 2007. Metode: Penelitian dilakukan pada pasien dengan fraktur manibular yang datang ke Rumah Sakit Hasan Sadikin Bandung. Data dikumpulkan secara retrospektif dengan cara mencatat etiologi,mekanisme, dan lokasi terjadinya fraktur mandibula. Data dikumpulkan dan dikelompokkan kemudian dianalisis dengan uji statistik Chi-square. Hasil: Dari hasil didapatkan 83 kasus fraktur mandibula. Fraktur mandibula lebih sering terjadi pada laki-laki yaitu sebanyak 77% dibandingkan wanita 22,9%. Fraktur mandibula sering terjadi pada usia 21-30 tahun, yaitu sebanyak 31orang (37,3%). Fraktur mandibula lebih banyak disebabkan tabrakan motor yaitu 71 orang (85,5%). Fraktur parasimfisis merupakan yang terbanyak yaitu 47 orang (56,6%). Kesimpulan: Penelitian ini dapat disimpulkan bahwa antara etiologi dari fraktur mandibula, mekanisme trauma dengan pola fraktur mandibula tidak terdapat hubungan yang bermakna.